Pengaruh Manajemen Talenta dan Work-Life Balance terhadap Retensi Karyawan Generasi Z pada Perusahaan Swasta di Kota Tebing Tinggi - Dwi Nopita Sari; Fuji Asih Aini; Dina Rina Junita; Fitria Masbulan Dalimunthe; Fifi Yunita Harahap; Fanny Sasbuhky Daulay; Aisyah Siregar (CV. ITTC INDONESIA, 2026)
Changes in work patterns and the demands of the new generation have made employee retention a strategic issue for private companies in Tebing Tinggi. Generation Z tends to change jobs easily if they feel they are not growing and lack work-life balance. In this context, talent management and work-life balance are two key factors believed to significantly influence Generation Z employees’ decisions to stay with a company. This study aims to examine the effect of Talent Management and Work-Life Balance on Generation Z Employee Retention in private companies in Tebing Tinggi City. A quantitative approach was employed using a sample of 96 respondents, determined by the Cochran formula. Data were collected through a Likert-scale questionnaire and analyzed using IBM SPSS Statistics with multiple linear regression analysis. The results indicate that Talent Management has a positive and significant effect on Employee Retention (Sig. = 0.002), while Work-Life Balance also has a positive and significant effect on Employee Retention (Sig. = 0.000). Simultaneously, both variables significantly influence Employee Retention (F = 24.248; Sig. = 0.000). The coefficient of determination (R²) of 0.343 indicates that 34.3% of the variation in Employee Retention is explained by Talent Management and Work-Life Balance, while the remaining 65.7% is influenced by other factors outside the research model. These findings suggest that effective talent management and work-life balance practices play an important role in improving Generation Z employee retention.